2014
DOI: 10.1007/s12013-014-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Kurarinone Synergizes TRAIL-Induced Apoptosis in Gastric Cancer Cells

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been identified as a promising anti-tumor agent against in a variety of cancers. However, gastric cancer cells are less sensitive than other cancer cells to TRAIL-induced apoptosis. Here, we combined TRAIL with kurarinone, a natural compound, to induce apoptosis in gastric cancer cell lines SGC7901. After the cells were treated with TRAIL and/or kurarinone, the cell viability and apoptosis were examined by MTT and flow cytometry, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Second, resistant mechanism of TRAIL-induced apoptosis is disrupted through downregulation of cFLIP expression. Natural compounds such as kurarinone (20), icaritin (21), withanolide E (22) were reported to downregulate cFLIP expression and subsequent sensitization of TRAIL-resistant cancer cells to TRAIL-induced apoptosis. Natural compounds, such as silibinin (23), gingerol (24) and indomethacin (25) were reported to possess both mechanisms of sensitizing TRAIL-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Second, resistant mechanism of TRAIL-induced apoptosis is disrupted through downregulation of cFLIP expression. Natural compounds such as kurarinone (20), icaritin (21), withanolide E (22) were reported to downregulate cFLIP expression and subsequent sensitization of TRAIL-resistant cancer cells to TRAIL-induced apoptosis. Natural compounds, such as silibinin (23), gingerol (24) and indomethacin (25) were reported to possess both mechanisms of sensitizing TRAIL-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some of the agents that their combined using with TRAIL has been acceptable outcomes but in limited cell lines have been listed below. kurarinone (Seo et al, ; Zhou, Cao, Wang, & Wu, ), monensin (Yoon et al, ), paxiline (Kang et al, ), diclofenac/hyaluronic acid (Dic/HA) (Fecker et al, ), nickel2+ (Schmidt et al, ), SHetA2 (Lin et al, ), BAY 11–7085 (Shen et al, ), compound c (Jang et al, ), FAK inhibitor PH11 (Dao et al, ), caffeic acid phenethyl ester (CAPE) (Li, Wu, et al, ), fasudil (Wang et al, ), cathepsin S inhibitor ZFL (Seo et al, ), 4‐(4‐Chloro‐2‐methylphenoxy)‐N‐hydroxybutanamide (CMH) (Bijangi‐Vishehsaraei, Huang, Safa, Saadatzadeh, & Murphy, ), actinomycin (Haimerl, Erhardt, Sass, & Tiegs, ), H1 (derivative of tetrandrine) (Lin, Wang, et al, ), genistein (Siegelin, Siegelin, Habel, & Gaiser, ), icaritin (Han, Xu, et al, ), ABT‐737 and VX–680 (Choi et al, ), 6‐shogaol (Han, Woo, et al, ), cathepsin E (Yasukochi, Kawakubo, Nakamura, & Yamamoto, ), ozarelix (Festuccia et al, ), transglutaminase 2 inhibitor (TGM2I) (Li, Xu, Bai, Chen, & Lin, ), amurensin G (Kim, Kim, Lee, et al, ), volasertib (Jeon et al, ), temozolomide (TMZ) (Zhitao, Long, Jia, Yunchao, & Anhua, ), chalcone‐24 (Xu et al, ), gingerol (Lee, Kim, Jung, Lee, & Park, ), triptolide (Chen et al, ), AKT inhibitor API‐1 (Li, Ren, et al, ), smac mimetic compounds (SMC) (Cheung et al, ), dicoumarol (Park, Min, Choi, & Kwon, ), partenolide (Trang et al, ), Pyrrolo‐1, 5‐benzoxazepine (PBOX) (Nathwani et al, ), embelin (Siegelin, Gaiser, & Siegelin, ), myricetin (Siegelin, Gaiser, Habel, & Siegelin, ), quercetin (Jung, Heo, Lee, Kwon, & Kim, ), silibinin (Son et al, ), epigallocatechin gallate (EGCG) (Abou El Naga et al, ), icariside II (Du et al, ), anisomycin (Seo et al, ), dioscin (Kim, Kim, Park, et al, ), celecoxib (Chen et al, ), micro RNA 126 (MiR‐126) (Zhang, Zhou, Zhu, & Yuan, ), gambognic acid (Ye et al, ), survivin inhibitor YM155 (Woo, Min, Seo, &...…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%
“…Kurarinone is one of prenylated flavonones isolated from the roots of Sophora flavescens . Pharmacological study suggested that kurarinone exhibited estrogenic (De Naeyer et al, 2004), anti‐microbial (Chen et al, 2005), anti‐cancer (Xie et al, 2018; Yang et al, 2018; Zhou, Cao, Wang, & Wu, 2015), anti‐virus (Pan, Yu, Yan, & Zhang, 2005) activities. Kurarinone possessed urinary bladder‐relaxant effect depending on the potentiation of large‐conductance Ca 2+ ‐activated K + channels (Lee et al, 2016) and immune regulation effects (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%